ANALISIS KELAYAKAN BISNIS DITINJAU DARI ASPEK KEUANGAN PRODUK EKONOMI KREATIF ( Studi Kasus Pada Distro " Powernoise Merch " ) Kabupaten Malang - Friyan Dwi Kristanto; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This research aimed to describe the results of the business feasibility analysis creative economic products in financial feasibility aspect. This product is a products on the distribution of Powernoise Merch. The case study of this study is the Powernoise Merch distro business in Malang district. The results showed that Break Even Point Rp. 43.044.011 or 478 onpieces, Payback Period 2,11 years, Net Present Value Rp. 196.663.587, Profitability Index 2,8 , Average Rate of Return 49 % and Internal Rate of Return 36%. Based on finansial feasibility, Powernoise Merch is feasible to be developed. Keywords:Business Feasibility Analysis, Creative Economic Products, Financial Feasibility.